Fertiliser practice and yield losses in process potato crops grown in Canterbury, New Zealand. Issue 1 (2nd January 2016) - Reid, JB; Searle, BP; Sinton, SM; Michel, A; Meenken, ED; Brown, H; Roberts, A; Manning, M
ABSTRACT: In Canterbury, New Zealand, potato ( Solanum tuberosum L.) growers are concerned that current fertiliser inputs limit yields. We tested if increasing these inputs would enable the crops to achieve their potential yield ( Y pot ). In four crops, nitrogen (N), phosphorus (P) and potassium (K) fertilisers were applied at or double the growers' current rates. We also included two rates of calcium (Ca). Tuber yields were compared using ANOVA and by simulation using PARJIB, a nutrient response model. None of the crops achieved Y pot . Yield was unaffected by changes in K or Ca rate. Doubling N and P applications increased yield at one site only (where Y pot was largest but soil P and mineral N concentrations were least). Up to 21% of Y pot was lost because of factors not included in the PARJIB model. Except at the least fertile sites, increasing fertiliser rates is unlikely to improve yield until the non-nutritional causes of yield gaps are identified and remedied.